PEMODELAN TIME-LAPSE MICROGRAVITY UNTUK ESTIMASI PERUBAHAN MUKA AIRTANAH DI BANDUNG, JAWA BARAT - Eko Januari Wahyudi; Wawan Gunawan A. Kadir; Susanti Alawiyah; Setianingsih Setianingsih; Indra Gunawan; Dadi Abdurrahman (JURNAL SUMBER DAYA AIR, 2023)
ABSTRACT Studies related to groundwater monitoring using geophysical methods have been carried out since the 1990s. Surface gavity data with a scheme of relative gravimeter measurements is chosen for monitoring in urban areas because it is quite fast, easy, affordable, and relatively low-impact on the environment. The significance of the time-lapse microgravity method for the target of this study depends on changes in the mass of water in the aquifer layer below the surface. The research area in this study covers the city of Bandung and several surrounding areas with an interpolated grid coverage of (18 x 17) km2. Gravity changes were determined by six repeated surveys at the same observation points from 2010 to 2021. The aim of this research is to develop a method for estimating groundwater table changes based on time-lapse microgravity data modeling. The complexity of subsurface density changes is simplified for two parts related to near surface density changes and density changes in the intermediate aquifer layer. The trend of groundwater table data in 2010 is used as a reference to determine estimates for 2015, 2016 (February and August), 2019, and 2021. Modeling results for intermediate aquifers (confined groundwater system) provide changes in groundwater levels from 2010 with estimates reached ±23 meters, while the results of modeling at near surface (shallow groundwater level) indicate a groundwater level change of approximately ±8 meters from the year 2010.Keywords:       microgravity, groundwater, modeling, hydrology, aquifer. ABSTRAKStudi terkait pemantauan airtanah dengan metode geofisika telah dilakukan sejak tahun 1990-an. Data gravity di permukaan dengan skema pengukuran gravimeter relatif dipilih pada pemantauan di area perkotaan karena cukup cepat, mudah, murah, dan relatif tidak merusak lingkungan. Signifikansi metode time-lapse microgravity pada target studi ini bergantung pada perubahan massa air pada lapisan akuifer di bawah permukaan. Area penelitian pada studi ini mencakup Kota Bandung dan beberapa area di sekitarnya dengan cakupan luasan interpolasi grid (18 x 17) km2. Perubahan gravitasi ditentukan oleh enam kali survei berulang pada beberapa titik pengamatan yang sama sejak 2010 sampai 2021. Tujuan dari penelitian ini adalah mengembangkan metode untuk mengestimasi perubahan muka airtanah berdasarkan pemodelan data time-lapse microgravity. Kompleksitas perubahan densitas di bawah permukaan disederhanakan untuk dua bagian terkait perubahan densitas dekat permukaan dan perubahan densitas pada lapisan akuifer menengah. Kecenderungan dari data muka airtanah pada tahun 2010 digunakan sebagai acuan untuk menentukan estimasi pada tahun 2015, 2016 (Februari dan Agustus), 2019, dan 2021. Hasil pemodelan pada akuifer menengah (sistem airtanah tertekan) memberikan perubahan muka airtanah dari tahun 2010 dengan estimasi mencapai ±23 meter, sedangkan hasil pemodelan pada kedalaman yang lebih dangkal (muka airtanah dangkal) menunjukkan perubahan muka airtanah mencapai ±8 meter dari tahun 2010.Kata Kunci:             microgravity, airtanah, pemodelan, hidrologi, akuifer